E-064 Initial institutional experience with the axium prime extra soft coil for treatment of intracranial aneurysms. (23rd July 2017) - Almandoz, Delgado J; Kayan, Y; Scholz, J; Milner, A; Wallace, A; Fease, J; Mulder, M
Abstract : Purpose: This study's goal is to evaluate the safety and efficacy of the Axium Prime Extra Soft (ES) coil for treatment of intracranial aneurysms. Methods: We conducted a retrospective review of all consecutive patients with intracranial aneurysms treated with Axium Prime ES coils at a single center between January 26 th, 2016 and March 28 th, 2017. Baseline patient and aneurysm characteristics, procedural variables and complications were recorded. Aneurysm occlusion at angiographic follow-up was determined using the Roy-Raymond scale. Aneurysm retreatment was recorded. Results: 45 patients with 48 intracranial aneurysms were included, 36 women (80%). Mean age was 58.2 years (median 58 years, 36–92 years). 47 aneurysms were treated successfully with coils (98%). 17 aneurysms were ruptured (35%), 8 recurrent (17%) and 3 symptomatic (6%). Mean maximum aneurysm size was 5.7mm (median 5.2mm, 2.2-26.2mm), mean neck 2.8mm (median 2.6mm, 1-6.2mm), mean dome to neck ratio 1.7 (median 1.4, 0.9-11.5). Aneurysm locations were: 13 anterior communicating artery, 11 middle cerebral artery, 10 internal carotid artery, 5 anterior cerebral artery, 4 posterior communicating artery, 1 basilar tip, and 1 each posterior inferior cerebellar, superior cerebellar, posterior cerebral and persistent hypoglossal arteries. Aneurysm embolization techniques were: 23 balloon-assisted coiling (48%), 11 stent-assisted coiling (23%), 10 simple coiling (21%), 3 Pipeline/coiling (6%), and 1 aneurysm was treated with flow diversion after attempted coiling (2%). Mean total number of coils deployed per aneurysm was 3.5mm (median 3, 1-14). Mean number of Axium Prime ES coils deployed per aneurysm was 2.1mm (median 2, 1-7). Mean Axium Prime ES coil length as total coil length percentage was 55.1% (median 42%, 11.1-100%). Mean packing density was 35.2% (median 35.7%, 1.6-63%). There were 6 peri-procedural complications: 3 coil herniations during balloon-assisted coiling requiring stenting (6%), 1 intra-operative aneurysm re-rupture controlled with balloon inflation (2%), 1 small peripheral subarachnoid hemorrhage on post-operative day 1 (2%), and 1 subacute stent thrombosis on post-operative day 4 (2%). The subacute stent thrombosis resulted in the patient's death (2.2%). No other treatment-related complication resulted in a permanent neurological deficit or death. Overall mortality was 4.4%. Angiographic follow-up was performed in 19 aneurysms (42%, 26 aneurysms currently pending follow-up). Follow-up was completed with MR angiography in 17 aneurysms (90%) and catheter angiography in 2 aneurysms (10%). Mean time to follow-up was 6.3 months (median 6.1 months, 5.9-7.6 months). At follow-up, 14 aneurysms were completely occluded (74%, Raymond 1) and 5 showed residual neck (26%, Raymond 2). There were no residual aneurysms at follow-up (Raymond 3). No aneurysms were retreated. Conclusion: The Axium Prime ES coil is safe and effective for the treatment of intracranial aneurysms, achieving high packing densities, low risk of major treatment-related complications, high medium-term complete/near-complete aneurysm occlusion rates, and low re-treatment rates. Disclosures: J. Delgado Almandoz: 2; C; Medtronic Neurovascular. Y. Kayan: 2; C; Medtronic Neurovascular. J. Scholz: None. A. Milner: None. A. Wallace: None. J. Fease: None. M. Mulder: None.